Physical education problems of 5–9 grade pupils in the context of health preservation - Идрисова, Наталия (Slobozhanskyi Herald of Science and Sport, 2017)
Natalia Idrisova Purpose: determination of the causes of deterioration of health and related problems of physical education of 5–9 grade pupils. Material & Methods: analysis of the causes and definition of the behavioral characteristics of pupils in relation to physical education was studied during 2012–2017 in one parallel class. In the experiment conducted in two stages, 52 pupils of the secondary school No. 1 of Melitopol took part. In the study used questionnaires, analytical, comparative, experimental and statistical methods. Result: tendency of deterioration of pupils health during training in middle classes is proved; obtained data in accordance with the typology compiled reflect the awareness of some students health as a means of raising the status, as well as the failure to understand half the researched values of physical education in maintaining health and disinterest in physical education. Conclusion: problems of school physical education are determined by the low level of the culture of health of the entire Ukrainian society.